The Influence of Law Enforcement on Restorative Justice-Based Conflict Resolution within the Customary Law in Aceh, Indonesia - Abdullah, M Adli; Mansur, Teuku Muttaqin; Masrizal, Masrizal; Muhammad Rasyid, Laila; Priyono, Ery Agus (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
The Indigenous People Community (IPC) in Aceh engages in collaborative efforts with law enforcement agencies to mediate disputes via customary courts, as delineated in Aceh Qanun Number 9 of 2008 pertaining to the Advancement of Customary Life and Traditions. Nevertheless, the escalating preeminence of formal legal frameworks has elicited apprehensions regarding the efficacy of customary sanctions in the context of community-driven conflict resolution. The objective of this research endeavor is to scrutinize the function of the police within the sphere of customary dispute resolution and to investigate the implications of their involvement on the jurisdiction of customary law institutions at the village level. The methodological approach employed in this inquiry is descriptive, supplemented by an empirical methodology. Primary data were acquired through direct observation and interviews with pivotal stakeholders, while secondary data were procured from ancillary documentation. The findings indicate that despite the successful resolution of 18 cases at the village level, the influence of the police tends to eclipse the authority of customary courts. The effectiveness of customary sanctions diminishes when formal law is accorded precedence, particularly in instances such as livestock theft or minor violent offenses. The conclusions that can be inferred suggest that excessive police involvement undermines the robustness of customary law, thereby contravening Article 13 paragraph (3) of Aceh Qanun 9/2008, which stipulates a preference for resolution through customary means at the village level.